Avifauna del centro de investigaciones costeras La Mancha, Veracruz, México - Ortiz Pulido, Raúl; Gómez De Silva G, Héctor; González García, Fernando; Alvarez A., Adriana (Instituto de Ecología, A.C., 1995)
We report the results of ornithological observations carried out in the Centro de Investigacione.s Costeras La Mancha, Veracruz, México, through 1989 to 1993. After more than 1040 h of observations we found 250 bird species belonging to 49 families. The richest families were Emberizidae (61 species), Tyrannidae (29), Accipitridae (16) and Ardeidae (12), We present information about the seasonality, relalive abundance, habitat and diet of all recorded species. Resident species were 46%, North American migrants (37%), and transients (13%), Migratory birds occur in this area from July to May, with higher numbers in November, February and March. Fifty percent of bird species are rare, 23% are scarce and 27% are common, Most species are invertebrates feeders (84%), frugivorous (36%) and vertebrates feeders (35%), The habitat with higher species recorded was the dune with shrubs (118 species), tropical pastures with isolated standing trees (117 species), tropical deciduous forest (89 species), and tropical semideciduous forest (89 species). However, 49 species living in the area are threatened in some way.